Interventions for smoking cessation in hospitalised patients - Rigotti, NA; Clair, C; Munafo, MR; Stead, LF (Cochrane Collaboration, 2012)
Background Smoking contributes to reasons for hospitalisation, and the period of hospitalisation may be a good time to provide help with quitting.